Of power, devotion and betrayal: a collection of Malaysian princesses’ folklores / Fawnnyna Menon and Ameiruel Azwan Ab Aziz - Menon, Fawnnyna; Ab Aziz, Ameiruel Azwan (Academy of Language Studies, 2023)
The increasing technological modernity has caused Malaysian folklore to head towards the side line as a mere bygone of the past. As one of the attempts to bring back and revive known and forgotten folklores to the Alpha generation, a 3-in-1 storybook containing four penned adaptations of our local folklores was created and is available in three versions; e-book, physical book, as well as illustrative narration videos of the stories was produced. The project aims to reignite the interest in Malaysian folklore among children so that it will not die in time. Besides, this project also aims to teach children new vocabulary and test their understanding. Moreover, it also can be used to introduce reading lessons to the children using local folklore. Developing ‘Of Power, Devotion and Betrayal: A Collection of Malaysian Princesses Folklores’ required a meticulous process of analysing, writing, illustrating, animating, as well as finalising the final product of the project. This project could contribute to resuscitating remnants from the past using future technology.